Surveying the Effect of the Phenol Compounds on Antibacterial Activity of Herbal Extracts: In vitro Assessment of Herbal Extracts in Fasa-Fars Province - Elahe Ahmadi; Abbas Abdollahi; Sohrab Najafipour; Mohamad Hasan Meshkibaf; Mehdi Fasihi Ramandi; Najmeh Namdar; Sara Abdollahi Kheyr Abadi; Seyyed Mohammad Mousavi; Babak Samizadeh; Ghader Allahverdi (Fasa University of Medical Sciences, 2016)
Background & Objectives: Due to increase in  bacterial drug resistance, discovering new antibacterial compounds is really important. The objective of this study is to evaluate the phenol compounds effect on antibacterial activity of herbal extracts of Fasa-Fars province in vitro. Materials & Methods: The antibacterial activity of 26 plants was studied by disk diffusion, well, and MIC methods in compare with 13 standard antibiotics against S. aureus and E. coli as control bacteria. Measurement of phenol compounds were performed by Seevers and Daly colorimetric methods using Folin-ciocalteu indicator. Results: Inhibition zone of bacterial growth  against S. aureus in well and disk methods were 32 and 22 mm in using Zataria multiflora, respectively .And there were 23 and 16 mm against E. coli in Zataria multiflora, respectively. Less effects and inhibition zones, less than 15mm on both strains, were seen in using  Saturina hortensis, Cinamomum zeylanicum, Artemisia absinthium, Urtica dioica, Carum carvi L. cyminum Cuminum, Achillea fragrantissimia, Marticaria chamomilla, Zingiber officinale, Origanum majorana, and Plantago psyllium. Most effective MIC results, 7.8 µg/ml, were related to the extracts of Zataria multiflora, Carum copticum L. Rosmarinus officinalis L., and Laurus nobilis L. Phenol compound amounts were approximately between 66.51±1.9 and 233.15±5.1 mg/gr extract in Zataria multiflora and Plantago psyllium, respectively. Conclusion: Results of antibacterial activity of extracts and relation with phenol compound amounts indicate the antibacterial effect of phenol compounds in herbal extracts.